A novel feline herpesvirus vector subunit FCV VP1 and FPV VP2 vaccine protects cats against FHV-1 and FPV challenge and induces serum neutralizing antibody responses against FCV - Tang, Aoxing; Li, Bo; Zhu, Meng; Zhu, Shiqiang; Zhang, Da; Li, Na; Zhang, Miao; Zhu, Yingqi; Li, Chuanfeng; Meng, Chunchun; Zhu, Jie; Liu, Guangqing (Frontiers in Immunology, 2025)
Vaccines targeting feline parvovirus (FPV), feline calicivirus (FCV), and feline herpesvirus type 1 (FHV-1) are considered core vaccines and are widely recommended for feline immunoprophylaxis. Currently, trivalent feline vaccines used in clinical settings are primarily based on inactivated or modified live attenuated formulations. Among these pathogens, FHV-1 has demonstrated notable potential as a viral vector due to its large genome and immunogenic profile, making it an attractive platform for multivalent vaccine development. In this study, we developed a novel trivalent live attenuated vaccine candidate by engineering FHV-1 as a viral vector to co-express immunogenic proteins from FPV and FCV. Using homologous recombination and CRISPR/Cas9-mediated genome editing, we constructed the recombinant strain FHV ΔgI/gE/TK-FCV VP1-FPV VP2, which expresses FCV VP1 and FPV VP2. Expression of these proteins was confirmed by Western blot and immunofluorescence assay (IFA), and the recombinant virus remained genetically stable during in vitro passaging. Immunization with this construct induced robust virus-neutralizing antibody responses and conferred protective immunity against both FHV-1 and FPV. These findings underscore the feasibility of using FHV-1 as a multivalent viral vector and provide a promising foundation for next-generation feline vaccines.